Application of Vegetable Composting Method Takakura with Temperature and pH Control Based on Internet of Things - Soelistianto, Farida Arinie; Rahmadhani, Aulia; Hidayati, Nurul (Politeknik Negeri Malang, 2023)
Compost is organic material that is decomposed in a place that is protected from the sun and rain. Factors that affect the success of composting are temperature, pH and light intensity in raw materials, types and sizes of raw materials. Waste processing carried out by the community is still conventional with a long time of 60 days so that by reprocessing waste simply by making Takakura basket compost which is done naturally for 30 days. The purpose of this research is to create a monitoring system for composting types of vegetables and fruits based on the internet of things using temperature sensors, pH sensors and light intensity sensors. The measurement results taken will be sent to firebase and displayed on the WEBSITE. The ESP32 microcontroller will process the value taken by the sensor and displayed on the LCD and WEBSITE in real time. Based on the test results, the temperature sensor is used to detect the basket temperature with an average value of 27-39°C. The temperature is more than 35°C then the fan will turn on. The pH sensor is used to detect acidity levels in vegetable and fruit compost. The light intensity sensor is used to detect sunlight received for photosynthesis when the afternoon light intensity value is below 1800 lux, the light will turn on to help photosynthesis in composting. WEBSITE display can be accessed well from 0.002307s delay and 93.3% packet loss.